Penyampaian Pesan Moral Hadis Pada Anak Usia Dini Melalui Metode Mendongeng Cas Cis Cus - Nur Sa'adah; Muqowim Muqowim (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2020)
This research describes the method of learning the proper hadith for early childhood. Hadith presentation for early childhood requires the creativity of a teacher so that the moral message contained in Hadith can be conveyed. In addition to considering the role of learning Hadith, the Nash Hadith, the content of Hadith messages, methods of delivery is also important to note that learning is as effective as possible. This research is done by using library research. Data collection is conducted by analyzing various media-shaped posts such as books, journals, and articles. From the analysis of the results, the method of storytelling of Cis Cus Cas is effective on learning Hadith to convey the moral message of hadith to early childhood. From the analysis of the method of storytelling, Cas Cis Cus is the right method for conveying the moral message of the hadith because in its implementation it gives a sense of happiness and moral education for early childhood.